Vagrants and visitors in the avifauna of the Haswell archipelago, East Antarctica - Golubev, Sergey (Polish Polar Research, 2020)
The purpose of the work is to provide a comprehensive review of the available historical and current records of vagrant and visiting individuals sighted at the Haswell archipelago, near the Russian Antarctic station Mirny (Davis Sea, southern Indian Ocean), from 1956 to 2016. Three rare vagrant species (eight observations) were recorded: the Chinstrap Penguin (Pygoscelis antarctica), Macaroni Penguin (Eudyptes chrysolophus) and Kelp Gull (Larus dominicanus). The Southern Giant Petrel (Macronectes giganteus; ten observations) and Pomarine Jaeger (Stercorarius pomarinus; a single observation) were visitors of the archipelago. Southern Giant Petrels and all vagrant individuals are of southern origin, the Pomarine Jaeger is a Holarctic breeding species. A single vagrant (and one uncertain case) appeared in the austral spring, and another eight – in the summer. Three cases of visitors were recorded in the austral spring, and eight in the summer. Records of vagrancy and visitors cover the dynamic period of changes in ice conditions. While most vagrants and visitors were sighted only for one day, two Macaroni Penguins stayed for several days at the archipelago. The most detailed issues in this work are those related to the study of vagrancy. I evaluate the possibilities of limited existence of vagrants and visitors into groups of endemic species as well as interspecific interactions. I also discuss the physical condition of vagrant individuals and factors contributing to their survival, ponder on the origin of vagrant individuals and visitors, their association with specific populations and causes of vagrancy.